Safety of butylated hydroxy anisole (BHA) for all animal species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Maryline Kouba; Mojca Kos Durjava; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2019)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety of butylated hydroxy anisole (BHA) for all animal species. In 2018, the Panel delivered an Opinion on the safety and efficacy of BHA. The Panel concluded that ‘a weight of evidence of the limited data supports that 150 mg BHA/kg complete feed would be a safe dose for all animal species. However, a possible exception could be cat, with its known lower capacity for glucuronidation of phenolic compounds and for which no specific data were available’. The Applicant submitted a review of the metabolism of phenolic compounds in cats and an in vivo study with cats. No specific information on metabolic fate of BHA has been made available for the feline species. The lack of knowledge is of particular relevance considering the additional load of phenolic compounds by dietary BHA for the full lifetime expectancy of cats. Owing the shortcomings in the design and reporting, the in vivo study could not be used to conclude on the safety of BHA for cats. Consequently, the Panel reiterates that no safe concentration of BHA in complete feed for cats could be established.